Nano-enhanced diets: advancing sustainability in aquaculture - a review - Anisa Mitra; Folasade Damilola Amulejoye; Prabal Barua; Sheu G. Odu-Onikosi; Payoja Mohanty; Hala Saber Khalil; Sahya Maulu (Cogent Food & Agriculture, 2025)
Aquaculture is the fastest-growing food sector and is essential for global food production and nutrition security. Continuous advancement with future innovations is therefore necessary for sustainability. In aquafeed, traditional feed additives have been used to enhance the nutritional value of formulated diets. Recently, nanotechnology has shown the potential to improve feed formulation and reduce the environmental impacts of aquafeeds. This research examines the use of nanotechnology to improve fish feed formulation for enhanced sustainability in aquaculture, focusing on how nanoparticles as dietary additives can boost nutrient availability, feeding efficiency, growth performance, and health in aquatic species. Results show that nano-enhanced diets improve fish growth performance, health, and environmental sustainability by enhancing nutrient efficiency and minimizing waste. Nanoparticles such as selenium, zinc, and iron have demonstrated notable benefits in enhancing fish growth, antioxidant defense, and disease resistance. However, challenges include nanoparticle toxicity, high costs, and regulatory concerns. While nanotechnology shows great promise in transforming aquaculture feed, its long-term environmental and health impacts require careful and thorough evaluation. This study advances sustainable aquaculture by providing new insights into integrating nanotechnology into fish diets, aiming to optimize aquafeed for improved productivity and sustainability.